(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Analyzing the characteristics of drug interactions occurring in outpatient prescriptions at the Department of Obstetrics and Gynecology, Tan Chau Regional General Hospital in 2019. Subjects and methods: Cross-sectional descriptive study on 400 outpatient treatment prescriptions stored at the Department of Obstetrics and Gynecology, Tan Chau Regional General Hospital, An Giang Province from January 1st, 2019 to December 31st, 2019. Results: 42.08% (101) of the prescriptions with drug interaction were found in the health insurance group and 42.50% (68) in the service examination group. 9.75% looked up the drug interaction, homogeneously from 2 drug interaction softwares and 16.00% of homogeneous drug interaction from 3 softwares. The rate of drug interaction software was related to prescriber’s qualification, examination mode and number of diagnosed diseases. The health insurance group of drug interaction were looked up from 2 identical software, accounting for 10.83% (2 softwares) and 16.25% (3 softwares) higher than that of service examinaiton 7.50% (2 softwares) and 15.63% (3 softwares). For the professional level of the prescriber with level 2 specialist accounted for the rate of drug interaction from2 homogeneous softwares was 15.38%, with master degree, the rate of drug interaction from 3 homogeneous softwares was 27.59%. Conclusion: The rate of drug interaction in the group of health insurance examination was higher than that of the service examination group. The rate of drug interaction software was related to prescriber’s qualifications, examination mode and number of diagnosed diseases.